Determinasi Behavioral Intention Pada Mahasiswa Pengguna Aplikasi BCA Mobile di Jakarta Timur - Ranisya Refanka Adhar; Ryna Parlyna; Osly Usman (INDO PUBLISHING, 2026)
This study aims to explore the connection between trust, perceived ease of use, perceived enjoyment, and perceived usefulness towards user’s behavioral intention on BCA Mobile application. Through the framework, this study examines how trust, perceived ease of use, perceived enjoyment, and perceived usefulness influence their behavioral intention to use BCA Mobile application. This study also adopts perceived usefulness as a mediating variable that mediates the relationship between independent variables and dependent variables. The research method was conducted using quantitative methods through questionnaire instruments and purposive sampling with 100 college student respondents in East Jakarta who use the BCA Mobile application. Data processing was analyzed through structural equation modeling (SEM) with the partial least squares (PLS) method and using Smart PLS 4 software. The results showed that (1) trust has no effect on perceived usefulness, (2) perceived ease of use has a significant effect on perceived usefulness, (3) perceived enjoyment has a significant effect on perceived usefulness, (4) perceived usefulness has no effect on behavioral intention, (5) perceived usefulness didn’t mediate trust’s influence on behavioral intention, (6) perceived usefulness didn’t mediate perceived ease of use’s influence on behavioral intention, and (7) perceived usefulness didn’t mediate perceived enjoyment’s influence on behavioral intention.